Trends in initiation of regular cigarette smoking in 28 European countries, 1940–2019: retrospective reconstruction from repeated cross-sectional surveys - Ayaka Teshima; Olivia Bannon; Filippos T Filippidis; Ariadna Feliu; Silvano Gallus; PERUGA URREA, ARMANDO; Cristina Martínez; Esteve Fernández (Oxford University Press (OUP), 2025)
Abstract In the European Union (EU), one in five youth currently smoke, with over half establishing regular smoking by age 18. Yet, evidence on the historical trends of smoking initiation remains scarce despite its importance for tobacco control. Using four waves of the Special Eurobarometer survey (2012–20; n = 110 753, aged ≥15), we retrospectively estimated trends in initiation rates (IRs) of regular cigarette smoking in the EU from 1940 to 2019 among individuals aged 10–24 by sex, region, and country for each calendar decade. EU-wide smoking IRs have decreased compared to the peak period, with narrowing disparities by sex and region. For males, the IRs have declined from 5.7% (95% CI = 5.6–5.9) in the 1970s to 3.2% (95% CI = 3.0–3.3) in the 2010s, and for females from 3.9% (95% CI = 3.7–4.0) in the 1990s to 2.4% (95% CI = 2.3–2.5) in the 2010s. The decline was more pronounced among young adults aged 18–24 than minors aged 10–17, with minors’ IRs surpassing those of young adults during the 2010s. Marked declines occurred among young adults in all regions, while among minors, a clear decrease was observed only for males in Northern Europe. Concerningly, the IRs among minors have trended upward in Eastern Europe for both sexes. Despite declining youth smoking initiation, an unacceptably high number of European youth still begin smoking regularly before the legal age of 18. Stricter and comprehensive tobacco control policies targeting youth, along with smoke-free generation initiatives, could substantially reduce future tobacco use and smoking-related mortality.